The 4 meters Bruckner test: An important tool in amblyopia screening of children with intellectual disability - Iulia-Andrada; Ana-Maria Dragan; Marius Bembea (Amaltea Medical Publishing House, 2019)
The screening of amblyopia in children with special should be performed with a rapid and objective examination, such as the Bruckner test. The hypothesis was that the 4 meter Bruckner test performed on special needs children could be at least as useful, if not superior to the 1 meter Bruckner test. The purpose of this study was to determine the sensitivity and specificity of the Bruckner reflex at 1 meter compared to 4 meters for the detection of ametropia and strabismus in intellectual disabled children. Material and method. The study was conducted on thirty-four patients with intellectual disabilities. Four medical students performed the 1 meter Bruckner test and then the 4 meter Bruckner test. After the test, all the patients underwent a full ophthalmological assessment, performed by the expert. The Fischer exact test and Chi square test were used to compare the results. Results. The 1 meter Bruckner test sensitivity was between 0 and 50% and the 4 meter Bruckner test was 55.6%-72% (p < 0.05). The 1 meter Bruckner test specificity was 85.7-100%, while the 4 meter Bruckner test was 81.1-93.8%(p < 0.05). Conclusions. Extending the distance of assessment between the examiner and the patient from 1 meter to 4 meters improves the ametropias detection accuracy.